COMPARATIVE STUDY MODELING OF GROUND WATER USING GEOGRAPHIC INFORMATION SYSTEM IN KAYUAMBON VILLAGE, BANDUNG BARAT REGENCY - Widiawaty, Millary Agung; Dede, Mohammad; Ismail, Arif (Indonesia University of Education, 2018)
Nowadays, fresh water availability is a problem and require serious attention from all parties. Urbanization in Kayuambon Village causes highly growth population and require fresh water to support the needs, it resources come from groundwater. This research aims to determine the groundwater direction and accumulation based on groundwater modeling using IDW, Kriging, Spline, and Minimum Curvature interpolation techniques. Result shows that Kriging interpolation technique has the highest validity then others with ME = 0.316833, RMSE = 10.68147, and R2 = 0.88934. Groundwater modeling results also found that Kayuambon Village has two cone of depression are located in the central and northern of the village which known as concentration of groundwater flow. This study is expected to be a consideration for people and stakeholders to realize sustainable groundwater utilization.